Evaluasi Kurikulum: Relevansi Ranah Afektif Dengan Pengamalan Sikap Toleransi dan Kepercayaan Diri - Ismail, Fajri (El-Idare, 2023)
The results of the affective domain assessment are not known to have a real impact on changes in students' everyday attitudes, such as tolerance and self-confidence, especially after Covid-19. This article aims to describe the relevance of the results of affective assessment to the practice of tolerance and self-confidence of students. The affective domain was chosen due to the fact that there is very little literature on affective evaluation and the practice of tolerance and self-confidence. The research method uses descriptive qualitative with a descriptive approach. Data were collected through observation, documentation and attitude scales, then analyzed using qualitative descriptive techniques. The conclusion of this study is First, the relevance of the results of the affective domain assessment was found with an attitude of tolerance in three aspects, namely (a) accepting other people's customs and culture, (b) listening to other people, (c) collaborating and discussing with other people in a very high category, and Moderate relevance category on the aspect of understanding other people's point of view. Second, the relevance to the attitude of self-confidence was found to be very high on the aspects of self-love and self[1]knowledge, and the relevance to the medium category was on the aspect of being at peace with oneself and having clear goals.